Efficacy and safety of bicyclol for treating patients with idiosyncratic acute drug‐induced liver injury: A multicenter, randomized, phase II trial. (25th May 2022) - Tang, Jieting; Gu, Jin; Chu, Naihui; Chen, Yu; Wang, Yongliang; Xue, Dongying; Xie, Qing; Li, Lei; Mei, Zaoxian; Wang, Xiaojin; Li, Jun; Chen, Jun; et al.
Abstract: Background and Aims: Evidence for using bicyclol in drug‐induced liver injury (DILI) is limited. This study aimed to explore the efficacy and safety of bicyclol in acute DILI. Methods: This was a multicenter, randomized, double‐blinded, double‐dummy, active‐controlled, superiority and phase II trial. Patients with idiosyncratic acute DILI were randomized 1: 1:1 to low‐dose bicyclol (25 mg times a day [TID]), high‐dose bicyclol (50 mg TID) and polyene phosphatidylcholine (control) groups. The primary endpoint was the decrease from baseline in serum alanine aminotransferase (ALT) levels at post‐treatment for 4 weeks. Results: Overall, 241 patients were included in the full analysis set, with 81, 82 and 78 patients in the low‐dose bicyclol, high‐dose bicyclol, and control groups respectively. ALT levels decreased across groups (−249.2 ± 151.1, −273.6 ± 203.1, and −180.8 ± 218.2 U/L in the low‐dose bicyclol, high‐dose bicyclol and control groups, respectively; both p  < .001, the bicyclol‐dependent groups vs. control group). The ALT normalization rates at weeks 1, 2, 4, 6 and 8 were higher in the bicyclol‐dependent groups than in the control group ( p  = .002 at week 1 and all p  < .001 at weeks 2, 4, 6 and 8 respectively). The median times to ALT normalization in the low‐dose bicyclol, high‐dose bicyclol and control groups were 29, 16 and 43 days respectively. Adverse events, serious adverse events and adverse drug reactions were similar across groups. Conclusions: Bicyclol (25 and 50 mg TID) appeared efficacious and safe for treating idiosyncratic acute DILI, while bicyclol 50 mg TID showed higher efficacy. Trial Registration Number: www.Clinicaltrials.gov (registration no. NCT02944552).